Clinical Outcomes and Patterns of Traumatic Injuries Associated with Subway Incidents at a Level 1 Trauma Center - Bharti Sharma; Aubrey May B. Agcon; George Agriantonis; Sittha Cheerasarn; Navin D. Bhatia; Zahra Shafaee; Jennifer Whittington; Kate Twelker (Life)
Objectives: Subway-related accidents have risen with advancements in the system. We aim to study the injury patterns from these incidents. Methods: This is a retrospective study from a single center, covering patients from 1 January 2016 to 31 December 2023. Patients were identified using International Classification of Diseases (ICD) injury descriptions and Abbreviated Injury Scale (AIS) body regions. Results: Out of 360 patients (total), 23.5% presented with head injuries with an AIS score ≥ 3. Patients with blunt trauma (93.99%) were in higher numbers than penetrating (5.74%) and burn trauma (0.3%). Overall, the mean Injury Severity Score (ISS) was 10.69, suggesting a broad range of traumatic injuries. ISSs for severe injuries (17–24) comprised 9.2%, moderate injuries (10–16) comprised 17.5%, and minor injuries (1–9) comprised 60.8%. Falls had the highest percentage of traumatic brain injuries (TBI) (65.60%) and fractures (67.50%). Assaults showed a significant occurrence of traumatic thoracic injuries (28.90%). Suicide attempts demonstrated a high percentage of traumatic amputations (30.80%). In the emergency department (ED), most patients (69.4%) were admitted for further care, such as trauma, neurosurgery, or other care. Of these patients, 0.5% died in the ED, 0.5% died on arrival, and 1.04% died within 15 min of arrival. The mortality rate among serious fall patients was 17.20% compared to the suicide and train-struck groups at 37.90% each. Conclusions: There were high occurrences of TBIs, and fractures, thoracic injuries, and amputations. Numbers of patients with blunt trauma were a lot higher than those with penetrating and burn trauma. The mortality rates observed in the suicide and train-struck groups were higher than those in patients with severe falls.